Real-Time Monitoring: Development of Low Power Fire Detection System for Dense Residential Housing Based on Internet of Things (IoT) and Cloud Messenger - Muhendra, Rifki; Amin, Aisyah (Universitas Negeri Semarang, 2021)
Purpose: This paper reports on the development of a low-power fire potential monitoring system for densely populated housing based on IoT Study design: This system consists of sensors integrated with a microcontroller and a Wi-Fi module that can provide data in real-time and can be accessed remotely. In addition, this system has also been simulated to analyze environmental conditions as notification data sent using cloud messenger. The grouping of potential fire hazards based on the legibility of physical parameter values is also displayed. Findings: In performance measurement, the data loss of this system is less than 1% of the total data every day. Value: It shows that this system is feasible and applied more broadly to anticipate fires in densely populated areas.